2001
DOI: 10.2460/ajvr.2001.62.1969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of racing and training on serum thyroid hormone concentrations in racing Greyhounds

Abstract: Except for total T4, thyroid hormone concentrations in Greyhounds are affected little by sprint racing and training. Greyhounds with low resting total and free T4 concentrations may not be hypothyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
2
31
2
1
Order By: Relevance
“…Studies of Greyhounds have shown that they have their basal TT4 concentrations below the non-breed-specific reference range, and that their fT4 concentrations are also relatively low, although not to the same degree as TT4. No significant differences were detected between the concentrations of cTSH in Greyhounds and other breeds (Hill et al 2001;Gaughan and Bruyette 2001). Similar results were also found in Whippets, where the mean TT4 values were significantly lower in comparison to the control group, but no significant differences were seen between Whippets and control dogs for fT4 and cTSH (Geffen et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…Studies of Greyhounds have shown that they have their basal TT4 concentrations below the non-breed-specific reference range, and that their fT4 concentrations are also relatively low, although not to the same degree as TT4. No significant differences were detected between the concentrations of cTSH in Greyhounds and other breeds (Hill et al 2001;Gaughan and Bruyette 2001). Similar results were also found in Whippets, where the mean TT4 values were significantly lower in comparison to the control group, but no significant differences were seen between Whippets and control dogs for fT4 and cTSH (Geffen et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…23 Most Greyhounds with low resting T4 and fT4 concentrations are not hypothyroid. 24 Therefore, hypothyroidism may have been overdiagnosed in this study population.…”
Section: Discussionmentioning
confidence: 87%
“…After sprint racing, total T 4 but not fT 4 concentration decreased after adjustment for hemoconcentration (Hill et al, 2001). After sprint racing, total T 4 but not fT 4 concentration decreased after adjustment for hemoconcentration (Hill et al, 2001).…”
Section: Athletic Trainingmentioning
confidence: 89%